Helmet for Body Temperature Measurement and Accident Location Detector With Telegram - Muhammad Nur Fahmi Febriansyah; Indah Sulistiyowati; Syamsuduha Syahrorini (Universitas Muhammadiyah Sidoarjo, 2022)
The increasing number of accidents among online motorcycle taxi drivers. The difficulty of monitoring the location of the accident on the driver is also due to the various paths traversed by the driver. Especially with the problem of the Covid-19 pandemic. Therefore, the purpose of this research is to create a tool that can track the whereabouts of online motorcycle taxi drivers in the event of an accident while also functioning as a Covid 19 detector through body temperature for online motorcycle taxi drivers which is applied to the helmet of the driver. The research method used in this research is by having several people detect their body temperature with the MLX90614 sensor on the tool and also by dropping the helmet as an indicator of an accident due to a collision with the helmet. In this study, the MLX90614 sensor is used to measure the body temperature of passengers and is displayed on the OLED display layer. To detect the accident using the FSR402 sensor which will be useful for detecting collisions on the helmet which will then send the point where the collision occurred via telegram bot. To detect the location using the GPS sensor Ublox Neo 6m. The results obtained by the MLX90614 sensor have an accuracy of 95% at an object distance of 5cm from the sensor. The reading from the FSR402 sensor is 1024 at the time of a collision or accident. And the Ublox Neo 6m GPS sensor is able to provide readings with an accuracy of about 99% for the longitude and latitude coordinates.